Flavonoid glycosides from the stem bark of Margaritaria discoidea demonstrate antibacterial and free radical scavenging activities. (22nd August 2013) - Ekuadzi, Edmund; Dickson, Rita; Fleischer, Theophilus; Annan, Kofi; Pistorius, Dominik; Oberer, Lukas; Gibbons, Simon
<x xml:space="preserve">Abstract</x> One new flavonoid glycoside, along with three known flavonoid glycosides were isolated from the stem bark of Margaritaria discoidea, which is traditionally used in the management of wounds and skin infections in Ghana. The new flavonoid glycoside was elucidated as hydroxygenkwanin‐8‐C‐[α‐rhamnopyranosyl‐(1 → 6)]‐β‐glucopyranoside (1) on the basis of spectroscopic analysis. The isolated compounds demonstrated free‐radical scavenging as well as some level of antibacterial activities. Microorganisms including Staphylococcus aureus are implicated in inhibiting or delaying wound healing. Therefore, any agent capable of reducing or eliminating the microbial load present in a wound as well as decreasing the levels of reactive oxygen species may facilitate the healing process. These findings therefore provide some support to the ethnopharmacological usage of the plant in the management of wounds. Copyright © 2013 John Wiley & Sons, Ltd.